A retrospective comparison of the conventional versus three-dimensional printed model-assisted surgery in the treatment of acetabular fractures - Öztürk, Anıl Murat (Acta Orthop Traumatol Turc, 2020)
OBJECTIVE: The aim of this study was to compare the clinical and radiological outcomes of the conventional versus individualized three-dimensional (3D) printing model-assisted pre-contoured plate fixation in the treatment of patients with acetabular fractures. METHODS: The data from 18 consecutive patients who underwent surgery for the acetabular fractures were retrospectively analyzed. The patients were divided into two groups (9 in each): conventional and 3D printed model-assisted. The groups were then compared in terms of the duration of surgery, time of instrumentation, time of intraoperative fluoroscopy, and volume of blood loss. The quality of the fracture reduction was also evaluated postoperatively by radiography and computed tomography in both the groups. The quality of the fracture reduction was defined as good (<2 mm) or fair (>2 mm) based on the amount of displacement in the acetabulum. RESULTS: The conventional group included 9 patients (9 males; mean age=41.7 years; age range=16–70) with a mean follow-up of 11.9 months (range=8–15); the 3D printed model-assisted group consisted of 9 patients (9 males; mean age=46.2 years; age range=30–66) with a mean follow-up of 10.33 months (range=7–17). The average duration of surgery, mean time of instrumentation, time of intraoperative fluoroscopy, and mean volume of blood loss were 180.5±9 minutes, 36.2±3.6 minutes, 6±1 times, and 403.3±52.7 mL in the 3D printed model-assisted group, and 220±15.6 minutes, 57.4±10.65 minutes, 10.4±2.2 times, and 606.6±52.7 mL in the conventional group, respectively. Procedurally, the average duration of surgery, mean time of instrumentation, and mean time of fluoroscopy were significantly shorter, and the mean volume of blood loss was significantly lower in the 3D printed model-assisted group (p<0.05). The quality of the fracture reduction was good in 7 patients (78%) in the conventional group and 8 patients (89%) in the 3D printed model-assisted group. CONCLUSION: As compared with the conventional surgery, the 3D printing model-assisted pre-contoured plate fixation technique can improve the clinical and radiological outcomes of the acetabular fractures, with shorter surgery, instrumentation, intraoperative fluoroscopy times, and blood loss. LEVEL OF EVIDENCE: Level III, Therapeutic study